RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI JASA SERVIS PADA CV DHARMA MOTOR - Rian, Hesti; Refriyanto, Bagus (POLITEKNIK LP3I JAKARTA, 2021)
The development of the Car Insurance Service Administration System is a web application where there are several inputs which include vehicle data, spare parts data, service data, and claim billing data. This research was conducted to design an administrative information system for car insurance services which is expected to help and simplify the billing of car insurance claims at CV Dharma Motor with system design using the Unified Modeling Language (UML) and the PHP programming language.Key words:information systems, Service administration, car insuranceThe development of the Car Insurance Service Administration System is a web application where there are several inputs which include vehicle data, spare parts data, Servis data, and claim billing data. This research was conducted to design an administrative information system for car insurance Service which is expected to help and simplify the billing of car insurance claimsat CV Dharma Motor with system design using the Unified Modeling Language (UML) and the PHP programming language. Key words:information systems, Service administration, car insurance